Using Technology-Mediated Task-Based Approach in Foreign Language Classes (El-Wahat Journal for Research and Studies, 2023)
Abstract:  Research in the field of foreign language teaching found a plethora of language teaching approaches all with the aim of giving both teachers and students a good teaching/learning experience. The task-based approach (TBA) of language teaching was one of those attempts and its synergy with technology became an interest to scholars in the field of language teaching. Therefore, this  paper offers insights into the characteristics of technology-mediated task-based language instruction, its advantages, and barriers to its successful implementation. Keywords: task-based approach, technology, technology-mediated language learning, technology-assisted language learning, technology-mediated  task-based instructions.الملخص:توصل البحث في مجال تدريس اللغة الأجنبية إلى عدد كبير من مناهج تدريس اللغة بهدف منح المعلمين والطلاب تجربة تعليمية / تعليمية جيدة. كان النهج القائم على المهام (TBA) لتدريس اللغة أحد تلك المحاولات وأصبح تعاونه مع التكنولوجيا محل اهتمام الباحثين في هذا المجال إذا كان تدريس اللغة. لذلك ، تقدم هذه الورقة نظرة ثاقبة لخصائص تعليم اللغة القائم على المهام بوساطة التكنولوجيا ومزاياها والعوائق التي تحول دون تنفيذها الناجح.كلمات دالة:  النهج القائم على المهام ، التكنولوجيا ،تعلم اللغات بمساعدة التكنولوجيا، التعليم القائم على المهام بوساطة التكنولوجيا